Design of IoT-Based Smart Hydroponic Farming with Solar Energy for Sustainable and Precision Crop Production - Monika Faswia Fahmi; Deni Tri Laksono; Dedi Tri Laksono (Fakultas Teknik Universitas Bhayangkara, 2025)
Conventional hydroponic farming systems frequently encounter limitations related to unstable environmental control, suboptimal nutrient management, and strong dependence on grid-based electricity, which collectively hinder their sustainability and scalability, particularly in remote or energy-constrained regions. Recent studies have explored smart hydroponic technologies. However, many remain reliant on external power sources or lack integrated, autonomous control of multiple critical growth parameters. Therefore, this problem reveals a research gap in the development of fully self-powered and intelligent hydroponic systems. This study proposes the design and implementation of a solar-powered, IoT-based smart hydroponic farming system that enables real-time monitoring and closed-loop environmental control. The system integrates multi-sensor measurements, including pH, DS18B20 temperature, total dissolved solids (TDS), and light-dependent resistor (LDR) sensors, coupled with an on–off control strategy to regulate light intensity (115 ADC), water temperature (28 °C), pH (5.5-6.5), and nutrient concentration (840 ppm). A standalone photovoltaic energy subsystem, consisting of a 100 Wp solar panel and a 65 Ah battery, was designed based on a daily energy demand of 378.85 Wh to ensure continuous autonomous operation. Experimental results demonstrate high sensor accuracy, with measurement errors of 0.75% for pH, 0.095% for TDS, and 0.24% for temperature. Moreover, the proposed system effectively stabilizes environmental parameters within predefined setpoints, outperforming uncontrolled conditions. These findings confirm the system’s reliability and potential as a sustainable precision agriculture solution for off-grid hydroponic applications.